2003
DOI: 10.3141/1857-09
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Traffic Flow Conditions in an Urban Network: Comparison of Multivariate and Univariate Approaches

Abstract: Several univariate and multivariate models have been proposed for performing short-term forecasting of traffic flow. Two different univariate [historical average and ARIMA (autoregressive integrated moving average)] and two multivariate [VARMA (vector autoregressive moving average) and STARIMA (space–time ARIMA)] models are presented and discussed. A comparison of the forecasting performance of these four models is undertaken with data sets from 25 loop detectors located in major arterials in the city of Athen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(172 citation statements)
references
References 19 publications
3
167
0
2
Order By: Relevance
“…It is also not shown how these models can be generalized to work for arbitrary road network topologies and more complex correlation structure. Existing multivariate parametric traffic prediction models [41], [42] do not quantify uncertainty estimates of the predictions and impose rigid spatial locality assumptions that do not adapt to the true underlying correlation structure.…”
Section: Related Work a Models For Predicting Spatiotemporallymentioning
confidence: 99%
“…It is also not shown how these models can be generalized to work for arbitrary road network topologies and more complex correlation structure. Existing multivariate parametric traffic prediction models [41], [42] do not quantify uncertainty estimates of the predictions and impose rigid spatial locality assumptions that do not adapt to the true underlying correlation structure.…”
Section: Related Work a Models For Predicting Spatiotemporallymentioning
confidence: 99%
“…The framework also allows the analyst to control the degree of data abstraction and generalisation and achieve a suitable trade-off between the model quality and model complexity, i.e., the number of different statistical models that represent the entire spatio-temporal variation. Kamarianakis and Prastacos (2003) compared several methods for modelling spatio-temporal data and found that a global spatio-temporal model does not necessarily perform better than a set of local temporal models. One of the arguments in favour of a global model was the excessive computational time needed for building multiple local models in case of a very large dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The related work in vehicular mobility prediction comes from the two main communities, i.e., the transportation system community [1], [2], [9], [22] and the vehicular networking community [13], [14]. From the first community, some works investigate the vehicular behavior prediction in terms of trajectories and routes [1], [6]- [9], [22].…”
Section: Related Workmentioning
confidence: 99%
“…of the resource of networks of roads and transportation systems, becomes a hot research topic that attracts broad interests [2]. On the other hand, newly emerged vehicular communication networks are seen as a key technology to help in relieving the traffic congestion and improving road safety, by building intelligent transportation systems [3]- [5].…”
mentioning
confidence: 99%